Selection of superior phosphorus starvation tolerant rice (Oryza sativa)genotypes using parent offspring regression and MGIDI - N, AANANTHI; G, RAIZA CHRISTINA; YASEEN, S K MOHAMED; NIRUBANA, V; RAMALINGAM, J (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2019–20 winter (rabi) (Oct–Jan) and late rabi 2020 (Jan–May) seasons at Agricultural College and Research Institute, Killikulam, Tamil Nadu to evaluate F₃ and F₄ segregating populations of the cross Anna (R) 4 × IR 64 Pup1 for phosphorus use efficiency, grain yield and related agronomic traits in rice (Oryza sativa L.). Significant genetic variability was observed for key traits, including grain yield, plant height, shoot phosphorus content and acid phosphatase activity. Estimates of phenotypic and genotypic coefficients of variation, heritability and genetic advance indicated moderate to high scope for genetic improvement, particularly for grain yield and phosphorus use efficiency. Skewness and kurtosis patterns across generations revealed shifts in genetic architecture, suggesting ongoing segregation and response to selection. Traits such as shoot phosphorus content and grain length-breadth ratio exhibited high heritability and strong intergenerational correlations, reflecting their stability across generations. Multi trait selection using the Multi trait Genotype Ideotype Distance Index (MGIDI) identified 10 superior genotypes, with AI- 48 showing the most desirable overall trait profile. Overall, the study demonstrates the potential for developing phosphorus efficient rice cultivars through the combined action of additive and non-additive genetic effects. The findings provide valuable insights for breeding programmes targeting high yielding rice genotypes adapted to phosphorus limited environments, thereby supporting more sustainable rice production.